Blood lipids profile in hyperlipidemic children undergoing different dietary long chain polyunsaturated supplementations: a preliminary clinical trial. (May 2014) - Verduci, Elvira; Agostoni, Carlo; Radaelli, Giovanni; Banderali, Giuseppe; Riva, Enrica; Giovannini, Marcello
Abstract The aim of this preliminary study was to explore the effect size of different dietary long chain polyunsaturated supplementations on blood lipid profile in children with primary hyperlipidemia. Thirty-six children (8–13 years) were recruited. After an 8-week stabilization period on the Step I diet, they were randomized to additionally receive for a 16-week period one capsule (500 mg) daily of docosahexaenoic acid (DHA) alone or a DHA plus eicosapentaenoic acid (EPA) mixture (45.6% DHA; 41.6% EPA) or wheat germ oil (control). An effect size (as percentage change from baseline) of +8%, −12% and −16% for high-density lipoprotein cholesterol (HDL-C), total cholesterol/HDL-C ratio and triglycerides was observed in children supplemented with DHA, compared to +2%, −8% and −12%, respectively, in children supplemented with DHA plus EPA. This preliminary study suggests powered trials appear feasible and are warranted to evaluate efficacy of n-3 long-chain polyunsaturated fatty acid dietary supplementations on the blood lipid profile of children with primary hyperlipidemia.